Electronic states of an ordered oxide on C-terminated 6H-SiC - Maier, Florian; Ristein, Jürgen; Ley, Lothar; et al. (Surface Science, 1999)
An ordered oxide monolayer with (√3×3√3)R30° periodicity was obtained on carbon-terminated 6H-SiC(000̄3) after preparation with a hydrogen microwave plasma. The stoichiometry of this surface was investigated by X-ray-induced photoelectron spectroscopy. Most components of the Si 2p, C 1s, and O 1s core lines are in agreement with the recently published atomic structure of this ordered monolayer. Beyond this we found hydrocarbon contamination that could be removed by annealing, and small graphitized areas remaining on the surface. We used angle-resolved ultra-violet photoelectron spectroscopy to examine the electronic structure of the valence band. Besides the O 2s and the O 2p lone pair state at 24 eV and 6 eV respectively below the valence band maximum (VBM), we detected a dangling bond state slightly above the VBM and a Si hybrid-O 2p-derived bonding state dispersing between 9.1 and 11.0 eV below the VBM. For the dangling bond state the possibility of a Mott-Hubbard ground state is discussed. In order to clarify the origin of the oxygen-derived states our results are compared with previous investigations of silicon oxides.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.electr